2019
DOI: 10.1016/j.commatsci.2019.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Aging and rejuvenation during elastostatic loading of amorphous alloys: A molecular dynamics simulation study

Abstract: Using molecular dynamics simulations, we investigate the effect of uniaxial elastostatic compression on the potential energy, structural relaxation, and mechanical properties of binary glasses. We consider the three-dimensional Kob-Andersen binary mixture, which was initially cooled from the liquid state to the glass phase with a slow rate at zero pressure. The glass was then loaded with a static stress at the annealing temperature during extended time intervals. It is found that the static stress below the yi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 42 publications
(76 reference statements)
3
39
0
Order By: Relevance
“…This definition was first introduced by Falk and Langer and used to identify accurately the location of shear transformations in strained disordered solids [40]. More recently, the spatiotemporal analysis of nonaffine displacements was applied to investigate shear band formation in steadily [12][13][14]42] and periodically [21,23,25,29,30,34] driven amorphous solids, as well as the structural relaxation in thermally cycled [43,44] and elastostatically loaded [45] glasses. Interestingly, the accumulation of atoms with large nonaffine displacements along the xy plane, shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This definition was first introduced by Falk and Langer and used to identify accurately the location of shear transformations in strained disordered solids [40]. More recently, the spatiotemporal analysis of nonaffine displacements was applied to investigate shear band formation in steadily [12][13][14]42] and periodically [21,23,25,29,30,34] driven amorphous solids, as well as the structural relaxation in thermally cycled [43,44] and elastostatically loaded [45] glasses. Interestingly, the accumulation of atoms with large nonaffine displacements along the xy plane, shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously found that the nonaffine measure is particularly well suited for identification of localized shear transformations in quiescent and deformed disordered solids [40][41][42]. More recently, the analysis of nonaffine displacements was used to elucidate the structural relaxation dynamics and yielding during time periodic deformation [14, 16, 18, 20-22, 27, 30, 31] and thermal processing [43][44][45][46][47] 8]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are a number of experimental techniques that can be used to increase the stored energy; namely, high pressure torsion, ion irradiation, wire drawing, and shot peening. Moreover, it was shown that prolonged static loading below the yield stress can induce either irreversible structural rearrangements or the formation of nanocrystals in the metallic glass matrix, leading to improved plasticity [5][6][7][8][9][10][11]. Alternatively, aged glasses can be rejuvenated by recovery annealing above the glass transition temperature and then cooled down with a suitably fast rate [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%